The performance of anammox reactor during start-up : enzymes tell the story - Lin, Qiujian (2020)
Start-up is the first and essential step in the operation of anammox (anaerobic ammonia oxidation) reactor. It is helpful to know the progress of start-up for the real-time optimization of reactor performance. In this work, a start-up mode was successfully established, by which the anammox reactor was smoothly put into use, with NLR (Nitrogen Loading Rate) and NRR (Nitrogen Removal Rate) of 11.0 and 10.1 kg-N /(m3 d), respectively. During the start-up, the dehydrogenase, alkaline phosphatase, hydrazine oxidase and heme of the anammox granular sludge were investigated and their activity/content was correlated with the reactor performance. The activity of dehydrogenase and alkaline phosphatase was found to decrease with the elevation of NLR. On the contrary, the hydrazine oxidase activity and heme content were observed to increase with the elevation of NLR. Based on the relative enzyme level, an enzyme indicator system was created to monitor the start-up progress of anammox reactor.